Religiosity Moderation on the Effect of Reward System and Motivation on Work Performance - Hayat Hayat; Sumartono Sumartono; Choirul Saleh; Ratih Nur Pratiwi (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
The purpose of this study is to analyze the reward system on work motivation of the state civil apparatus and work performance, the effect of religiosity moderation on the influence of motivation on the work performance of the state civil apparatus and the effect of religiosity moderation on the effect of the reward system on the work performance of the civil apparatus country. The research method used quantitative research using WarpPLS 0.6 analysis. The results of research and discussion show that the reward system has a positive and significant effect on work motivation. More rewards given will have an impact on employee motivation. In addition, the effect of the reward system on work performance also has a positive and significant effect. In the aspect of Religiosity as moderation, motivation and work performance effect is insignificant and positively moderates both, even the tendency to weaken. The emphasis is that work does not only depend on competence, skill, and capacity, but must be supported by the belief that there is a God who is always at work, because serving the community is part of worship that rewards God will repay with multiplied kindness.